Assisting Reluctant Teachers College Students to Autonomously Appreciate a Novel to Read - Siusana Kweldju (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
Abstract This paper is a report of how to make reluctant teachers colÃÂlege students read in a prose course. These students were not interested in fiction and had never read interpretative fiction in English. The teacher sought to know why the students were reluctant to read, and how to make them read, and discovered that it was because of students linguistic deÃÂficiency and their reluctance to read longer texts. The teacher also disÃÂcovered that in spite of their reluctance they were interested in listening to the teachers explanation about the cultural elements and the analysis of the short stories. Thus, provided with a guideline developed based on cultural and gender elements, students were motivated to autonomously read an assigned Pulitzer-winning novel.